Features of ball impact in straight, curve and knuckle kicks in soccer - Kimachi, K.; Koido, M.; Hong, S.; Shimonagata, S.; Nakayama, M.; Asai, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The quantitative relationship between kicking motion and ball behaviour can be easily explained by detecting the impact point and foot posture. In previous studies, the impact point of a kicking foot was difficult to capture using visual tracking. Thus, a virtual surface modelling technique was applied in this study to clarify the differences in the three-dimensional foot speed, impact point and foot posture between straight, curve, and knuckle kicks in soccer, as well as the relationship between the kick motion and ball rotation. An optical three-dimensional motion capture system (VICON) was used to record the kicking motion. The impact points of the straight, curve, and knuckle kicks were found to be centrally located in the instep area, at a lower (more downwards) inside area, and at the medial area between the instep and inside areas of the kicking foot, respectively. Moreover, an impact with a greater `swing vector deviation angle (relative to the direction from the impact point to the centre of gravity of the ball)` is necessary for ball rotation. The impact point detection method employed in this study can be applied to other ball impact estimations beyond soccer kicks.